2016
DOI: 10.1136/heartjnl-2015-308949
|View full text |Cite
|
Sign up to set email alerts
|

Targeted multiple biomarker approach in predicting cardiovascular events in patients with diabetes

Abstract: GDF-15 and hs-TnT are strong independent cardiovascular biomarkers augmenting the predictive value of NT-proBNP in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Whether GDF-15 could be involved as the protector from atherosclerotic injury with similar molecular mechanisms as mentioned above is not sufficiently clear. Although some scientists reported that levels of GDF-15 in people with diabetes demonstrated the close positive association with traditional CV risk factors, such as LDL cholesterol, BMI, age, inflammatory activity, but not with TG [14,15]. The results of our study well correspond with these findings, and we yielded that GDF-15 could be a component of the endogenous vascular repair system that maintains vascular integrity and function.…”
Section: Discussionsupporting
confidence: 87%
“…Whether GDF-15 could be involved as the protector from atherosclerotic injury with similar molecular mechanisms as mentioned above is not sufficiently clear. Although some scientists reported that levels of GDF-15 in people with diabetes demonstrated the close positive association with traditional CV risk factors, such as LDL cholesterol, BMI, age, inflammatory activity, but not with TG [14,15]. The results of our study well correspond with these findings, and we yielded that GDF-15 could be a component of the endogenous vascular repair system that maintains vascular integrity and function.…”
Section: Discussionsupporting
confidence: 87%
“…EDTA plasma produces predictably lower NT‐proBNP values (10%‐13%) than those observed in serum or heparin plasma, which may be explained by NT‐proBNP fragmentation after samples are drawn . Additionally, heparinized whole blood can be analysed in point‐of‐care systems, a portable device measuring NT‐proBNP in real time . The ideal handling of BNP and NT‐proBNP samples in order to minimize pre‐analytical variations is not fully established .…”
Section: Cardiac Damage Biomarkersmentioning
confidence: 99%
“…Moreover, GDF-15 has able to identify a vulnerable subjects in general population without known CV disease, prediabetes and diabetes mellitus [23]. Resl, et al [25] reported that elevated level of GDF-15 have independently associated with subsequent CV event and 10-year all-cause mortality even after adjusting for well-established CV risk factors and widely used cardiac biomarkers (NT-pro brain NP, cardiac troponins, hs-C-reactive protein). However, there is not agreement regarding an issue about whether or not that an elevated GDF-15 level in peripheral blood is adaptive response in HF individuals aiming recovery of vascular function.…”
Section: Introductionmentioning
confidence: 99%
“…cardiac hypertrophy, HF, atherosclerosis, stable coronary artery disease, myocardial infarction, as well as in hypertension, diabetes mellitus, abdominal obesity, chronic kidney disease, and malignancy [22][23][24]. Recent clinical studies have shown that GDF-15 independently predicted allcause mortality rate and CV death rate in patients with coronary artery disease, atrial fibrillation and HFpEF and HFrEF [24,25]. Moreover, GDF-15 has able to identify a vulnerable subjects in general population without known CV disease, prediabetes and diabetes mellitus [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation